Los hechos gravados en el IVA en el derecho comparado - Villanueva Gutiérrez, Walker (Pontificia Universidad Católica del Perú. Fondo Editorial, 2014)
This article analyzes the definitions of the main taxable events for the Value-Added Tax (VAT) based on a comparative approach to thelegislation of different countries (Spain, Mexico, Chile, Colombia, Argentina and Peru). In this regard, it analyzes which legislations offer definitions according to the principles of generality, fiscal neutrality and legal certainty for VAT. Moreover, it points out that the VAT systems of those countries do not require as a condition for the configuration of the taxable events that the transactions involve a «value added» or a final consumption. In the specificcase of «supplies of goods», the VAT systems have a similar definition of the taxable event, although there are a few differences. However, in the case of«supplies of services», which is the most important taxable event for VAT, there are important differences at the time each country defines it. This is not a desirable effect for the international trade of services, since the lack of harmonization produces double taxation or double non taxation.

El trabajo aborda la definición de los hechos gravados principalesen el Impuesto al Valor Agregado (IVA) en el derecho comparado (España, México, Chile, Colombia, Argentina y Perú), evaluando qué legislaciones proponen una definición conforme a los principios de generalidad, deneutralidad y de seguridad jurídica. Destaca que ninguna de las legislaciones exige como condición para la configuración de los hechos gravados que setrate de transacciones que generen «valor agregado» o que se trate de bienes o servicios susceptibles de consumo final. En el caso de la venta de bienes muebles, hay coincidencia en la definición del hecho gravado, aunque con matices de diferencia. En cambio, en la definición de servicios, que es la hipótesis más importante del impuesto, hay grandes diferencias entre las legislaciones. Ello definitivamente no es deseable, considerando el comercio internacional de servicios, por cuanto la falta de armonización produce fenómenos de doble imposición y doble no imposición.
The taxable events for the Value-Added Tax (VAT) based on a Comparative Law approach
Keywords: Derecho comparado en el IVA; Definición de venta en el IVA; Definición de servicios en el IVA; https://purl.org/pe-repo/ocde/ford#5.05.00